Libary and information science parameters and perspectives: essays in honour of Prof.P B Mangla - Mangla, P B; Prasher, R G (Ed.) (New Delhi Concept, 1997)
This book is presented in two volumes.The contents of both the volumes would be useful for all those who are interested in the areas of LIS,IT,and application of IT in library work and services.
Contents: v.1. Library and information science: basic -v.2. Information science, information technology and its application
Keywords: Library science; Information science; Library education; Libraries; Information technology; Information services